2017
DOI: 10.1002/2016gc006785
|View full text |Cite
|
Sign up to set email alerts
|

Lithospheric thickness estimation beneathNorthwesternSouthAmerica from anS‐wave receiver function analysis

Abstract: We make use of the S‐to‐P receiver function technique beneath Colombia and neighboring regions to make a first‐order approximation of the depth of the Lithosphere‐Asthenosphere Boundary (LAB) and, therefore, of lithospheric thickness. A deconvolution technique was used to calculate the receiver functions, and after a moveout correction and a time‐depth conversion, LAB depths for different tectonic regions of northwestern South America were obtained. Results are typically between 65 and 110 km, consistent with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
31
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 22 publications
(37 citation statements)
references
References 60 publications
5
31
1
Order By: Relevance
“…Melting of the lithospheric or asthenospheric mantle in convergent margins may be either related to delamination after considerable crustal thickening, which may be commonly associated with extension (Kay & Kay, ), or to changes in the subduction angle (Kay et al, ; Kay & Mpodozis, ). For the EC, we favor shallowing of the slab as the main trigger mechanism, as neither the temporal association of this magmatism with compression (Mora et al, , ) nor the relatively uniform lithospheric thickness in the whole northern Andes region (Blanco et al, ) fit the delamination hypothesis. As the slab angle shallows, asthenospheric upwelling can trigger lithospheric melting (Li & Li, ).…”
Section: Discussion and Tectonic Implicationsmentioning
confidence: 82%
“…Melting of the lithospheric or asthenospheric mantle in convergent margins may be either related to delamination after considerable crustal thickening, which may be commonly associated with extension (Kay & Kay, ), or to changes in the subduction angle (Kay et al, ; Kay & Mpodozis, ). For the EC, we favor shallowing of the slab as the main trigger mechanism, as neither the temporal association of this magmatism with compression (Mora et al, , ) nor the relatively uniform lithospheric thickness in the whole northern Andes region (Blanco et al, ) fit the delamination hypothesis. As the slab angle shallows, asthenospheric upwelling can trigger lithospheric melting (Li & Li, ).…”
Section: Discussion and Tectonic Implicationsmentioning
confidence: 82%
“…The presence of this high-density trend down to 75 km depth suggest that it travelled with the mobile Caribbean lithosphere. Accordingly, Blanco et al (2017) reported the Lithosphere-Asthenosphere Boundary in the Caribbean region around 75-80 km depth.…”
Section: High Density Mantle Trend: Preserved Materials Of the Clip Plmentioning
confidence: 99%
“…The eastward extent of the flat slab south of the modern WBZ offset is unknown, but we propose that the eastern margin of the flat slab aligned itself with the Eastern Cordillera, much as the modern flat slab continues to do today. We propose this geometry because the eastern limit of the flat slab could be due to the presence of thicker lithosphere along and east of the Eastern Cordillera that hinders the farther eastward horizontal advance of the flat slab [e.g., Yarce et al, 2014;Blanco et al, 2017]. This geometry is also the simplest geometry that connects the ongoing active volcanism (and therefore ongoing normal subduction) at 3°N to the broadest portion of the modern flat slab just north of 5.5°N (Figure 3b).…”
Section: 1002/2017gl073981mentioning
confidence: 99%